Analisis Interpretasi Filsafat Stoisisme pada Buku Filosofi Teras Karya Henry Manampiring dan Relevansinya dengan Nilai-Nilai Ekstrinsik yang Terkandung di dalam Cerita Pendek - Desra Nita Tampubolon (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The study was set to examine an interpretation of the philosophy of the course and to elevate it with a short story extrapolated value found in the mega best seller on the self-improvement volume volume entitled "Filosofi Teras" by Henry Manampiring. The study is a library study using qualitative descriptive methods. The data-gathering technique in this study is text-reading with the data-analysis techniques using the elective analysis techniques, that is, analyzing, connecting and summarizing the study of philosophy and extrapolic values contained in the short story. The data analysis techniques in this study are based on data selectively, that is, data reduction, data presentation, and deduction drawing. The urgency of research is for readers to understand, possess and implement the values contained in the short story book Filosofi Teras and extrinsic values.